Method for recovering graphene coated SiO2 composite material prepared from wind power blade with assistance of fused salt and application of graphene coated SiO2 composite material
The molten salt method assists in the recovery of wind power blades and prepares graphene @SiO2 composite materials, which solves the problems of low recycling efficiency and the use of toxic chemical reagents in the prior art, and achieves efficient recycling and excellent performance battery negative electrode materials, providing technical guarantees for commercial applications.
Patent Information
- Application Number
- CN202411986019.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing technology is difficult to effectively recycle and utilize retired wind power blades, and the traditional recycling methods are cumbersome to operate, use toxic chemical reagents, and are inefficient, so it is impossible to achieve large-scale resource recycling and utilization.
The molten salt method is used to assist in the recovery of wind power blades. Graphene @SiO2 composite material is prepared by fully mixing the molten salt with the wind power blade powder and reacting under heating conditions. This method simplifies the process flow, reduces energy consumption and reaction time, and improves production efficiency.
Graphene @SiO2 composite material was successfully recovered and prepared, and applied to the negative electrode material of sodium ion battery, which significantly improved the conductivity and ion transport performance of pure wind power blade powder, showed excellent long cycle stability and rate performance, and provided technical guarantee for commercial applications.
Smart Images

Figure CN119774594A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of wind turbine blade recycling, and in particular relates to a method and application of molten salt-assisted recycling of wind turbine blades to produce graphene@SiO2 composite materials. Background Art
[0002] Wind power generation has become an important part of my country's energy development strategic action plan due to its advantages such as cleanliness, high efficiency and renewable energy. my country has become the country with the largest wind power installed capacity in the world. With the advent of the wind turbine retirement wave, retired wind turbine blades have become a large solid waste material that my country urgently needs to solve. Wind turbine blades are mainly made of glass fiber / carbon fiber / plant fiber reinforced composite materials. The reinforcing fiber in wind turbine blades is a high-strength and high-toughness material. The main components of the matrix material are: thermoplastic plastics (polyethylene, polyurethane, polypropylene and polyvinyl chloride) and thermosetting resins (epoxy resin, vinyl ester, polyester). At present, the main recycling methods for retired wind turbine blades can be divided into the following three categories: (1) mechanical recycling, (2) thermal recycling and (3) chemical recycling. The research team of Tongji University used recycled waste wind turbine blade particles to replace quartz sand in FRP pipes and developed a new type of glass fiber reinforced polymer composite material (glass fiber reinforced polymer) composite pipe. The experimental results of domestic and foreign researchers using various polar solvents, non-polar solvents, and inorganic solvents show that dichloromethane has good swelling properties for epoxy resin, small usage, and low reaction temperature. However, these recovery methods are cumbersome to operate, use toxic chemical reagents, and are inefficient, making it impossible to achieve large-scale resource recycling of retired wind turbine blades. Compared with other recovery methods, molten salts can greatly promote the interaction between reactants because molten salts can enhance the fluidity of reactants, and the reaction rate of molten salts is several times that of solid-state reactions. Moreover, molten salts have high solubility, and the final product can be removed from the solidified salt by simple washing and filtration. In addition, with the advent of the era of electric vehicles and smart grids, the shortage of lithium resources will become an important factor restricting their development, and sodium-ion batteries, with their abundant raw materials and low cost, have gradually become an important alternative to lithium-ion batteries. In the research of sodium-ion batteries, domestic and foreign scholars mainly focus on the development of electrode materials and the improvement of battery performance. Studies have shown that sodium-ion batteries have significant advantages in safety and environmental friendliness. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a method and application for recycling graphene@SiO2 composite materials from wind turbine blades assisted by molten salt. Based on the molten salt method, graphene@SiO2 (graphene-coated SiO2) composite materials are prepared by recycling wind turbine blades. Based on the obtained graphene@SiO2 composite materials, after being compounded with conductive carbon and binder, they are used as electrode materials and applied to negative electrode materials of batteries, such as negative electrode materials of sodium ion batteries, which can greatly improve the development obstacles of poor conductivity and ion transport performance of pure wind turbine blade powders. It is expected to provide technical support for the future commercial application of synthesizing graphene and silica composite materials from rapidly decomposing and recycling retired wind turbine blades in energy storage batteries.
[0004] The technical solution of the present invention is as follows:
[0005] A method for recycling graphene@SiO2 composite materials from wind turbine blades assisted by molten salt, comprising the following steps:
[0006] (1) Mix the molten salt and the wind turbine blade powder thoroughly to obtain a uniform mixture; the molten salt is one or more of LiCl, KCl, and NaCl;
[0007] (2) React the mixture at a reaction temperature T from room temperature to the reaction temperature T in an air or nitrogen atmosphere to obtain graphene@SiO2 composite materials (black powder).
[0008] The mass ratio of the molten salt to the wind turbine blade powder is (5-20):1.
[0009] The reaction temperature T is: the melting point of the molten salt < T < the boiling point of the molten salt.
[0010] The wind turbine blade includes resin and glass fiber.
[0011] The reaction time is 1 min to 2 h.
[0012] Step (2) also includes washing and drying.
[0013] The heating rate in step (2) is (1-100) °C / min.
[0014] The graphene@SiO2 composite material is a C-coated SiO2 structure, with the chemical formula C@SiO2. The graphene is amorphous, and its macroscopic morphology is thin-layered. The macroscopic morphology of SiO2 is fibrous, with a diameter of 10-20 μm.
[0015] The present invention also provides an electrode material based on the above graphene@SiO2 composite material, including the graphene@SiO2 composite material.
[0016] The electrode material also includes conductive carbon, a binder and a solvent. According to the mass ratio, graphene@SiO2 composite material: conductive carbon: binder = (5-9): (0.5-3): (0.5-1.5)
[0017] The conductive carbon is one or more of acetylene black, conductive graphite, nanographite, furnace black, Ketjen carbon black and carbon nanotubes.
[0018] The binder is one or more of polyvinylidene fluoride, butyl rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyimide and polytetrafluoroethylene.
[0019] The solvent is one or more of N-methylpyrrolidone, dimethylformamide, tetrahydrofuran, carbon tetrachloride, water and ethanol.
[0020] According to the mass ratio, solvent: solid matter = (4-12): 1; the solid matter is graphene@SiO2 composite material and conductive carbon.
[0021] The method for preparing the electrode material comprises the following steps:
[0022] (1) mixing and grinding the graphene@SiO2 composite material and the conductive carbon to obtain a mixture;
[0023] (2) Mix the binder and the solvent, stir for 15 minutes to 1 hour, add them into the mixture obtained in step (1), and stir for 8 to 20 hours to form a uniform paste, thereby obtaining an electrode material based on a graphene@SiO2 composite.
[0024] The present invention also provides an electrode plate, comprising a current collector and the above-mentioned electrode material located on the current collector.
[0025] The method for preparing the electrode sheet comprises the following steps:
[0026] (1) Coating current collector
[0027] The electrode material is evenly coated on the current collector, dried at 50-80° C. for 4 hours, and then placed in a vacuum dryer for 12-20 hours to obtain a dry current collector coated with the electrode material;
[0028] (2) Rolling treatment
[0029] The dried current collector coated with the electrode material is rolled and cut to obtain electrode plates.
[0030] In the step (1), the current collector is copper foil or aluminum foil.
[0031] In the step (1), the drying temperature of the vacuum drying is 50 to 80°C.
[0032] In the step (1), the active material loading per unit area on the current collector is 0.8 to 5 mg / cm 2 , the active material is a graphene and silicon dioxide composite material and conductive carbon.
[0033] The present invention also provides a negative working electrode, using the electrode sheet as the negative working electrode.
[0034] The present invention also provides a battery, comprising the working electrode negative electrode, wherein the battery is a lithium ion battery, a sodium ion battery or a potassium ion battery.
[0035] A method for preparing a sodium ion battery comprises the following steps:
[0036] In an argon environment, the electrode plate is used as a negative electrode, the sodium plate is used as a positive electrode, and the electrode plate, the sodium plate, a diaphragm and an electrolyte are assembled into a sodium ion battery.
[0037] The sodium ion battery of the present invention has a power consumption of 100 mA g -1 After 500 cycles at a current density of 1.34 W, the specific capacity remains at 80-110 mAh g -1 , the capacity retention rate is 100-100.64%. At the same time, at 5000mA g -1 After cycling at a high current density of 100 mA g -1 When the discharge reversible specific capacity is still maintained at 84.4 mAh g -1 .
[0038] The molten salt-assisted recycling of wind turbine blades to prepare graphene@SiO2 composite materials and their application have the following advantages and beneficial effects compared with the existing methods for recycling wind turbine blades:
[0039] 1. The present invention successfully recycles waste wind turbine blades using the molten salt method and synthesizes graphene @ SiO2 composite materials. The molten salt in the molten salt method provides a reaction system for recycling waste wind turbine blades; the graphene @ SiO2 composite materials recovered using the molten salt method can be applied to the battery field.
[0040] 2. The graphene@SiO2 composite material prepared by the molten salt-assisted recovery of wind turbine blade powder of the present invention has a special morphology and composition. The wind turbine blade recovery method is to heat from room temperature to (the melting point of the molten salt used to the boiling point of the molten salt used) at a heating rate of (1-100)°C / min, and keep warm for 1min-2h. The process is simple, with low energy consumption and short reaction time, which significantly improves production efficiency. In addition, the graphene morphology of the present invention is complete, and its preparation method does not generate other by-products, which truly realizes a short-process new process route for efficiently recycling waste wind turbine blades to directly prepare battery negative electrode material precursors.
[0041] 3. The graphene@SiO2 composite material recovered and prepared by the present invention is applied to the negative electrode material of sodium ion battery. After the sodium ion battery is prepared, during the charge and discharge process of the sodium ion battery, graphene can greatly improve the development obstacles of poor conductivity and ion transmission performance of pure wind turbine blade powder, and show excellent long-cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 are XRD diagrams, where (a) is the XRD diagram of the wind turbine blade used; and (b) is the XRD diagram of the graphene@SiO2 composite material prepared by molten salt assisted technology treatment and recovery.
[0043] Figure 2 are SEM images, where (a) is the SEM image of the wind turbine blade used; and (b) is the SEM image of the graphene@SiO2 composite material prepared by molten salt assisted technology.
[0044] Figure 3 TEM images and energy spectra of graphene@SiO2 composite materials prepared by molten salt-assisted technology treatment and recycling, where (a) is the TEM image of the graphene@SiO2 composite material, (b), (c), and (d) are the element distribution energy spectra of C, O, and Si elements in the graphene@SiO2 composite material, respectively.
[0045] Figure 4 The wind turbine blade powder and the sodium ion battery based on the graphene@SiO2 composite negative electrode material of Example 1 of the present invention are 100, 200, 500, 1000, 2000 and 5000 mA g -1 Rate performance diagram at current density of .
[0046] Figure 5 The sodium ion battery prepared based on the graphene@SiO2 composite negative electrode material of wind turbine blade powder and Example 1 of the present invention is 100mA g -1 Cyclic performance diagram after 500 cycles at a current density of . DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with embodiments.
[0048] In the following examples, unless otherwise specified, the raw materials and equipment used were all commercially available, and the purity of the raw materials was analytical grade.
[0049] Example 1
[0050] A method for preparing a graphene and silicon dioxide composite material by molten salt-assisted recovery of wind turbine blade powder is as follows:
[0051] The molten salt with a mass ratio of 10:1 was fully mixed with the wind turbine blade powder to obtain a uniform mixture A, wherein the molten salt was a eutectic salt of LiCl and KCl, wherein the mass percentage of LiCl was 59.2%. The mixture A was placed in a 150 mL corundum crucible and heated in a muffle furnace from room temperature to 400°C at a rate of 5°C min -1 The temperature was kept at 400°C for 30 min. After the heating process was completed, the muffle furnace was cooled to room temperature, and the product was directly collected from the corundum crucible and washed without further treatment. After drying, the graphene@SiO2 composite material was obtained as a black powder. The recovery rate was 50-90%.
[0052] The recycled graphene@SiO2 composite material was subjected to XRD, SEM and TEM test analysis, and its XRD pattern is shown in Figure 1 (b) Yes Figure 1 The XRD pattern in the graph is analyzed to obtain the chemical formula of the graphene@SiO2 composite material recycled and prepared in this embodiment as C@SiO2. There is a small amount of hexagonal silicon dioxide (PDF#01-086-1565; space group: P3221) in the wind turbine blade powder, and the calculated lattice parameter value is The graphene@SiO2 composite material synthesized by recycling wind turbine blade powder with the assistance of molten salt is amorphous, so there is no obvious characteristic peak intensity in the XRD diagram.
[0053] The SEM images of the wind turbine blade powder and the recycled graphene@SiO2 composite material used in this embodiment are shown in Figure 2 (a) and (b), from Figure 2 In (a), it can be seen that in the wind turbine blade powder, the silica fiber morphology is a fibrous structure with an average diameter of 10-20 μm, and there is resin material. Figure 2 In (b), it can be seen that thin layers of graphene and silica fibers exist in the graphene@SiO2 composite material prepared by molten salt recycling.
[0054] The TEM image and energy spectrum of the graphene@SiO2 composite material prepared by molten salt recovery in this example are shown in Figure 3 ,from Figure 3 It can be seen that there is a thin layer of graphene in the graphene@SiO2 composite material prepared by molten salt recovery, in which the silicon dioxide particles are coated with graphene. The energy spectrum can show that the thin layer material is graphene and the silicon dioxide is coated with graphene.
[0055] An electrode material based on a graphene@SiO2 composite material comprises the graphene@SiO2 composite material prepared as above, conductive carbon, a binder and a solvent; wherein, by mass ratio, the graphene and silicon dioxide composite material: conductive carbon: binder = 7:2:1.
[0056] The conductive carbon is carbon black, the binder is polytetrafluoroethylene, and the solvent is N-methylpyrrolidone.
[0057] The method for preparing the electrode material based on the graphene@SiO2 composite material comprises the following steps:
[0058] Weigh 70 mg of the graphene@SiO2 composite material, 20 mg of carbon black and 10 mg of polytetrafluoroethylene, mix and grind the graphene@SiO2 composite material and the carbon black to obtain a mixture;
[0059] 10 mg of polytetrafluoroethylene was added to 400 μL of N-methylpyrrolidone, stirred for 40 min, and then put into the above mixture, and magnetically stirred for 10 h to form a paste, thereby obtaining an electrode material based on graphene@SiO2 composite material.
[0060] An electrode plate comprises a current collector and the above-mentioned electrode material located on the current collector. The preparation method comprises coating the adjusted electrode material based on graphene@SiO2 composite material on copper foil, drying it at 60°C for 4 hours, then vacuum drying it at 60°C for 12 hours, rolling it, and cutting it into the electrode plate.
[0061] The electrode plate is used as the negative electrode material of a sodium ion battery.
[0062] The process of assembling the above-mentioned sodium ion battery negative electrode material into a button-type half-cell is as follows:
[0063] After the electrode sheet is sliced and pressed, it is assembled into a button-type half-cell in a glove box with a sodium sheet as a counter electrode. In the button-type half-cell, the diaphragm is a glass microfiber diaphragm (Whatman, 1823025) membrane, and the electrolyte is 1.0M NaPF6 (DIGLYME).
[0064] The assembled button-type half-cell was subjected to rate testing to investigate its cycle stability and rate performance. The rate curve is shown in Figure 4 .from Figure 4As can be seen in the figure, the graphene@SiO2 composite material has a -1 After cycling at a high current density of 100 mA g -1 When the discharge reversible specific capacity is still maintained at 84.4 mAh g -1 , which is significantly higher than that of wind turbine blade powder. This shows that the recycled graphene@SiO2 composite negative electrode material is not significantly damaged after the rapid embedding and extraction process, and has good stability.
[0065] The sodium ion battery prepared based on the recycled graphene@SiO2 composite negative electrode material in this embodiment is tested at room temperature for the cycle performance of the button-type half-cell. Figure 5 The results are as follows: At 100mA g -1 After 500 cycles at a current density of 1.34 W, the specific capacity remains at 80 mAh g -1 The capacity retention rate is 100.64%, which is significantly higher than that of wind turbine blade powder (49.2 mAh g -1 ).
Claims
1. A method for preparing graphene@SiO2 composite materials from wind turbine blades by molten salt-assisted recycling, characterized in that: It includes the following steps: (1)充分混合熔盐和风电叶片粉末,得到均匀的混合物;所述熔盐为LiCl、KCl和NaCl中的一种或几种; (2)在空气或氮气的氛围下,将混合物从室温加热至反应温度T进行反应,得到石墨烯@SiO2复合材料。 2. The method for preparing graphene@SiO2 composite materials by molten salt-assisted recovery of wind turbine blades according to claim 1, characterized in that: 所述熔盐与风电叶片粉末的质量比为(5~20):1。 3. The method for preparing graphene@SiO2 composite materials by molten salt-assisted recovery of wind turbine blades according to claim 1, characterized in that: 所述反应温度T为:熔盐的熔点<T<熔盐的沸点。 4. The method for preparing graphene@SiO2 composite materials by molten salt-assisted recovery of wind turbine blades according to claim 1, characterized in that: 所述风电叶片包括树脂和玻璃纤维。 5. The method for preparing graphene@SiO2 composite materials by molten salt-assisted recovery of wind turbine blades according to claim 1, characterized in that: 所述反应时间为1min~2h。 6. The method for preparing graphene@SiO2 composite materials by molten salt-assisted recovery of wind turbine blades according to claim 1, characterized in that: 步骤(2)还包括洗涤和烘干。 7. An electrode material, characterized in that: 包括权利要求1所述方法得到的的石墨烯@SiO2复合材料。 8. An electrode plate, characterized in that: 包括集流体和位于集流体上的权利要求7所述的电极材料。 9. A negative working electrode, characterized in that: 以权利要求8所述电极极片作为工作电极负极。 10. A battery, characterized in that: 包括权利要求9所述的工作电极负极,所述电池为锂离子电池、钠离子电池或钾离子电池。 It should be noted that there is an incorrect expression "权利要求1所述方法得到的的石墨烯@SiO2复合材料" in the original text, which may be a duplication error. It is recommended to check and correct the original text for more accurate translation. The above translation is based on the existing text. (1)充分混合熔盐和风电叶片粉末,得到均匀的混合物;所述熔盐为LiCl、KCl和NaCl中的一种或几种; Full mix the molten salt and the wind turbine blade powder to obtain a homogeneous mixture; the molten salt is one or more of LiCl, KCl, and NaCl; (2)在空气或氮气的氛围下,将混合物从室温加热至反应温度T进行反应,得到石墨烯@SiO2复合材料。 (2) Under the atmosphere of air or nitrogen, heat the mixture from room temperature to the reaction temperature T for reaction to obtain the graphene@SiO2 composite material. 所述熔盐与风电叶片粉末的质量比为(5~20):1。 The mass ratio of the molten salt to the wind turbine blade powder is (5 - 20):
1. 所述反应温度T为:熔盐的熔点<T<熔盐的沸点。 The reaction temperature T is: the melting point of the molten salt < T < the boiling point of the molten salt. 所述风电叶片包括树脂和玻璃纤维。 The wind turbine blade includes resin and glass fiber. 所述反应时间为1min~2h。 The reaction time is 1 min to 2 h. 步骤(2)还包括洗涤和烘干。 Step (2) also includes washing and drying. 包括权利要求1所述方法得到的的石墨烯@SiO2复合材料。 It includes the graphene@SiO2 composite material obtained by the method described in claim 1. 包括集流体和位于集流体上的权利要求7所述的电极材料。 It includes a current collector and the electrode material described in claim 7 located on the current collector. 以权利要求8所述电极极片作为工作电极负极。 Use the electrode sheet described in claim 8 as the working electrode negative electrode. 包括权利要求9所述的工作电极负极,所述电池为锂离子电池、钠离子电池或钾离子电池。 It includes the working electrode negative electrode described in claim 9, and the battery is a lithium-ion battery, a sodium-ion battery, or a potassium-ion battery.
Citation Information
Patent Citations
Internal pyrolysis treatment and recovery method for retired wind power blade
CN117644598A